Earthcasting: Geomorphic Forecasts for Society. Issue 11 (2nd November 2021) - Ferdowsi, Behrooz; Gartner, John D.; Johnson, Kerri N.; Kasprak, Alan; Miller, Kimberly L.; Nardin, William; Ortiz, Alejandra C.; Tejedor, Alejandro
Abstract: Over the last several decades, the study of Earth surface processes has progressed from a descriptive science to an increasingly quantitative one due to advances in theoretical, experimental, and computational geosciences. The importance of geomorphic forecasts has never been greater, as technological development and global climate change threaten to reshape the landscapes that support human societies and natural ecosystems. Here we explore best practices for developing socially relevant forecasts of Earth surface change, a goal we are calling "earthcasting". We suggest that earthcasts have the following features: they focus on temporal (∼1–∼100 years) and spatial (∼1 m–∼10 km) scales relevant to planning; they are designed with direct involvement of stakeholders and public beneficiaries through the evaluation of the socioeconomic impacts of geomorphic processes; and they generate forecasts that are clearly stated, testable, and include quantitative uncertainties. Earthcasts bridge the gap between Earth surface researchers and decision‐makers, stakeholders, researchers from other disciplines, and the general public. We investigate the defining features of earthcasts and evaluate some specific examples. This paper builds on previous studies of prediction in geomorphology by recommending a roadmap for (a) generating earthcasts, especially those based on modeling; (b) transforming a subset of geomorphic research into earthcasts; and (c) communicating earthcasts beyond the geomorphology research community. Earthcasting exemplifies the social benefit of geomorphology research, and it calls for renewed research efforts toward further understanding the limits of predictability of Earth surface systems and processes, and the uncertainties associated with modeling geomorphic processes and their impacts. Plain Language Summary: A major goal of the modern science of geomorphology is to better understand and more accurately predict how Earth surface systems (e.g., the landforms created by deposition of sediment carried by rivers, coastal dunes, hillslopes) respond to natural and human‐made forces, and to prepare for and mitigate surface hazards and events that may have major short and long‐term impacts (such as debris flows, flooding due to sea level rise, change in river landform, etc). In this paper, we discuss the necessary qualities of practicable Earth surface forecasts, which we call "earthcasts". We suggest that earthcasts are predictions for time‐scale ∼1–∼100 years and length‐scale of ∼1 m–∼10 km; they are developed with direct involvement of stakeholders and public beneficiaries through the evaluation of the socioeconomic impacts of Earth surface events; and they generate forecasts that are clearly stated, are testable, and include quantitative uncertainties. We further discuss challenges and basic and applied scientific developments and investments needed for developing more complete earthcasts. We also provide academic and governmental examples of such earthcasting efforts. Key Points: Earthcasts are testable forecasts of Earth surface change with quantified uncertainties, on spatiotemporal scales relevant to planning We discuss a potential avenue for direct involvement of stakeholders, which we argue is essential for an earthcast We provide near‐complete examples of earthcasts and suggest a roadmap for developing earthcasts as a part of research in geomorphology